a) (ym + 3) (ym - 3) =
b) (a + bc) (a - bc) =
c) (5m* - 7n**) (5m* + 7n**) =
d) (abc + 5g) (abc - 5g) =
e) (1/4 + ht) (1/4 - ht) =
f) (xy + 14) (xy - 14) =
g) (x/y + 9/4) (x/y - 9/4) =
h) (-5m + 2) (-5m - 2) =
i) (7/3m - 3n/2) (7/3m + 3n/2) =
j) (a + 5) (a - 5) =
k) (-5/9 + 5m) (-5/9 - 5m) =
l) (32 + mg) (32 - mg) =
m) (15h + 2/4) (15h - 2/4) =
n) (3m** + 13/5) (3m** - 13/5) =
ñ) (ab + cd) (ab - cd) =
nota: un asterisco (*) significa al cuadrado y dos asteriscos (**) significan al cubo.
No hay comentarios:
Publicar un comentario